PENGARUH PENDAPATANMASYARAKAT TERHADAP KONSUMSI DAGING SAPI DI DESA KOTABUNAN KECAMATAN KOTABUNAN KABUPATEN BOLAANG MONGONDOW TIMUR - Tadete, Muh Anshar; Elly, F H; Kalangi, L S; Hadju, R (ZOOTEC, 2016)
EFFECT OF INCOME ON BEEF CONSUMPTION IN KOTABUNAN VILLAGE EAST BOLAANG MONGONDOW REGENCY. Consumption of beef by society tends to increase in line with their income. The problem is whether people's income changes affectÂ  beef consumption. The purpose of this study was to analyze the effect of income on beef consumption. Research has been conducted in the village of Kotabunan, District of Kotabunan East Bolaang Mongondow Regency.The data collection was conducted using a survey method. The data used are primary and secondary data. Determination of the sample villages have been done by purposive sampling, the village which has the largest population, and in the coastal area. Sample was selected by simple random sampling. The number of respondents as many as 44 households..Simple regression analysis was used to meet the goal of this study. Based on the results showed total incomes of respondents Rp. 143,070,000 with an average of Rp. 3,251,590.9/household /month. Total beef consumption 63.5 Kg / month, with an average expenditure of respondents to consume beef Rp. 134,886.36 or 4.9% of family income. Consumption of animal protein from livestock as much as 6 grams / capita / day, equivalent to 10.3 kg of meat / capita / year, 6.5 kg of eggs / capita / year, and 7.2 kg milk / capita / year is still not achieved. Based on the results of this study concluded that incomes significantly affect the consumption of beef in the village Kotabunan, District Kotabunan, East Bolaang Mongondow Regency. Keywords : income, consumption, beef